Zanotti Fragonara, Luca - (:unkn) unknown (My University, 2026)
Dr Luca Zanotti Fragonara is Lecturer in the Centre of Autonomous and Cyber-Physical Systems and in the Aerospace Integration Research Centre. His research is focused on structural health monitoring, machine learning and system identification. He is involved in a series of high-impact research projects ranging from autonomous inspections of aerospace structures to structural health monitoring for increasing the resilience of industrial plants. He matured a wide and unique experience working in monitoring problems applied to civil, mechanical, aerospace and space structures. Moreover, his interests in machine learning applied to monitoring allowed him to expand his research activities to other areas, such as perception, tracking and sensor fusion. He has a solid knowledge in vibration problems, non-linear dynamics problems and in finite element modelling.